Comparison of Chemical Components and Biological Properties in Internal Tissue’s Dictyophora indusiata Extracts: Effects of Temperature and Solvent Systems (Early view) - Supawadee Patathananone, Sebrian Yusbani, Orathai Peethong; Wuttisak Kunu (Tropical Life Sciences Research, 2026)
Noncommunicable diseases (NCDs) pose significant public health challenges and have substantial economic impacts. Bioactive compounds represent promising targets for reducing the risk of NCD progression. This study aimed to extract chemical constituents from the internal tissue of D. indusiata mushrooms using 35 kHz ultrasonication at varying temperatures and with different solvents, and to compare extract yield, antioxidant activity, tyrosinase inhibitory activity, and cytotoxicity in normal cell lines, including Vero cells and hepatocyte growth factor (HGF) cells. In addition, total phenolic, flavonoid, and terpenoid contents were quantified, and compound profiles were characterised using thin-layer chromatography (TLC) and gas chromatography–mass spectrometry (GC–MS). The findings indicate that deionised water at 80 °C was the most effective extraction solvent. The extracts designated L-A3-02-80W and O-A3-01-80W yielded the highest levels of phenolics, flavonoids, and terpenoids, and also exhibited superior antioxidant and antityrosinase activities compared with other extraction conditions. Moreover, both extracts demonstrated low cytotoxicity towards Vero and HGF cells. Polyphenolic and flavonoid constituents displayed strong antioxidant signals on the TLC plates. Eight identical compounds were identified in both extracts, including tetradecanoic acid, decanoic acid silver(1+) salt, 2-azido-2,4,4,6,6-pentamethylheptane, trans-2,4-dimethylthiane, S,S-dioxide, trans-2-methyl-4-n-pentylthiane, S,S-dioxide, methyl 12,13-tetradecadienoate, 2-azido-2,4,4,6,6,8,8-heptamethylnonane, and 9-borabicyclo[3.3.1]nonane 9-(3-methoxycyclohexyl)oxy-. These findings provide preliminary evidence that extracts from the internal tissue of D. indusiata may represent promising candidates for further in vivo validation and formulation studies aimed at developing potential functional food applications.